Impact of urethroplasty on overactive bladder symptoms in patients with anterior urethral strictures. (3rd October 2021) - Hamamoto, Koetsu; Horiguchi, Akio; Shinchi, Masayuki; Ojima, Kenichiro; Hirano, Yusuke; Takahashi, Eiji; Kimura, Fumihiro; Ito, Keiichi; Azuma, Ryuichi
Abstract : Objectives: To investigate the incidence of overactive bladder in men with anterior urethral stricture and to evaluate the impact of urethroplasty on its improvement. Methods: A total of 104 men with anterior urethral stricture who underwent urethroplasty between 2016 and 2020 completed a validated urethral stricture surgery patient‐reported outcome measure comprising six lower urinary tract symptoms questions on voiding symptoms and overactive bladder symptom score before and 3, 6, and 12 months after urethroplasty. Patients with an urgency score of ≥2 for overactive bladder symptom score question 3, and a total overactive bladder symptom score of ≥3 were considered to have overactive bladder. An improvement in overactive bladder was defined as a decrease in the total overactive bladder symptom score by at least three points. Results: Thirty‐nine patients (37.5%) were considered to have overactive bladder, and improvement in overactive bladder after urethroplasty was found in 30 (76.9%). Maximum flow rate on uroflowmetry, postvoid residual urine volume, lower urinary tract symptoms total score, and total overactive bladder symptom score were all significantly improved after urethroplasty ( P < 0.0001 for all variables). There was a positive correlation between changes in lower urinary tract symptoms total score and total overactive bladder symptom score (Spearman's correlation 0.48, P < 0.0001). Multivariate logistic regression analysis showed that greater change in lower urinary tract symptoms score was an independent predictor of improvement in overactive bladder (odds ratio 1.30, 95% confidence interval 1.06–1.59; P = 0.002). Conclusions: Overactive bladder is prevalent in patients with anterior urethral stricture, and can be effectively improved after urethroplasty. Improvement of voiding symptoms are key for improving overactive bladder symptoms.